Analisis Yuridis Tindak Pidana Pembunuhan Biasa; Studi Kasus Berdasarkan Berita Acara Pemeriksaan Dari Laporan Polisi No:LP/B/62/III/2025/SPKT/POLRES MALAKA/POLDA NTTT - Samara, Finsensius; Lapudooh, Hensuf Meykhel; Fahiberek, Rafaelle Ciprianus; Ajang, Angelina Merici Putri Ndais; Ninu, Ursula Virginia Jessica; Oetnana, Cristian Mario (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This research juridically analyzes the ordinary murder crime based on the Investigation Report of Police Report Number LP/B/62/III/2025/SPKT/Polres Malaka/Polda NTT. The murder case occurred on March 21, 2025 in Naibesi Hamlet, Malaka Regency, with suspect SEBASTIANUS RUA TAE allegedly taking the life of victim MELIANA MAKO using a stone. This research employs a normative juridical method with statutory, case, and conceptual approaches. Analysis was conducted on the fulfillment of elements in Article 338 of the Criminal Code and evaluation of case file completeness for prosecution stage. Research findings indicate that the element of "whosoever" is fulfilled with clear identification of the suspect. The element of "intentionally" is proven through series of actions demonstrating suspect's awareness that his conduct could result in death. The element of "taking another person's life" is fulfilled by victim's death due to blunt force trauma causing severe bleeding, as confirmed by expert testimony in visum et repertum. Although criminal elements are fulfilled, the case file still requires refinement through confrontation to address inconsistencies in testimonies, completion of official visum et repertum documents, and deepening of murder motive before it can be declared complete (P-21) and transferred to prosecution stage.